REPRESENTASI PENGGUNAAN TEKNOLOGI MASYARAKAT KEKINIAN DALAM KOMIK DIGITAL TAHILALATS LINE WEBTOON - Oliviar, Joan; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT The growth in communication technologies makes people can never abandoned it’s technologies that have been influenced their social behavior in the modern/ contemporary society can be seen in Tahilalats comic by Nurfadli Mursyid in digital comic LINE Webtoon application. \5The strip comics largely raised the story of humor full of satire, especially when people are began to be controlled by communication technology. The purpose of this research is to find the representation of technology dependence of the contemporary society in comic strop LINE Webtoon Tahilalats. The type of this research is qualitative, with constructivist paradigm. The primary data sources of this research are Tahilalats comic strips episode 465 (Trending), 215 (waras), and 224 (Berbagi), which are contained in the LINE Webtoon digital comic application. This research method is semiotic analysis of Charles Sander Peirce. The result of this research, found that from each of the drawing comic panels in the three episodes of Tahilalats comic, represents a modern society that cannot be separated from technology, which meets the three stages of indicator in Marshall McLuhan technology determinism theory. The three stages are; discovery in communication technology leads to a cultural change; changes in the types of communications ultimately shape human life; communication technology provides a message and shapes/ create our own behavior.   Keywords: Ketut Budiana, Painting, Prabu Udayana, Representation of Leadership, Semiotics